Enhancing Financial Reporting Practices among Micro-Enterprises through Digital Literacy Campaigns and Computerized Accounting Systems - Minda Yustrisna Devi; Fitri Rahmiyatun (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study examines the impact of digital literacy campaigns and computerized accounting databases on the financial reporting practices of micro-enterprises in Indonesia. Micro-enterprises, which play a vital role in the Indonesian economy, often struggle with financial management due to limited knowledge and resources. To address these challenges, digital literacy campaigns were implemented to educate micro-enterprise owners on the benefits and usage of digital financial reporting tools. The primary objective of this research was to enhance financial literacy among these business owners and facilitate the adoption of computerized accounting systems, which are expected to improve the accuracy and efficiency of financial reporting. The study involved 50 micro-enterprises from various sectors, including food and beverage, fashion, and crafts. Data were collected using structured questionnaires and direct observations. The research aimed to assess how digital literacy campaigns could improve financial reporting practices, thereby supporting better financial decision-making and business sustainability. The digital literacy campaigns provided training on financial literacy, the importance of financial reports, and tips on obtaining funding using reliable financial reports. Additionally, computerized accounting templates were introduced to automate accounting processes, reduce errors, and save time, allowing business owners to focus on strategic aspects of their businesses. The findings of this research are expected to offer valuable insights and recommendations for policymakers, educators, and business owners. By highlighting the benefits of digital financial literacy and the importance of adopting digital tools, this study aims to drive the implementation of best practices among micro-enterprises. Ultimately, the research seeks to contribute to the growth and sustainability of micro-enterprises, thereby enhancing their role in the national economy.